Public Sector Budget Based on Systemic Agenda: What Factors Leading the Budget Change Policy in the Crisis Time in Indonesia? - Wulan Suci Rachmadani; Djoko Suhardjanto; Abdul Kharis Almasyhari; Wahyu Widarjo; Kusumaningdiah Retno Setiorini (Migration Letters, 2023)
This study examines the factors that influence the policy of budget changes during a crisis due to the impact of the COVID-19 Pandemic in Indonesia. It is quantitative research. The population of the study is local government throughout Indonesia. The sampling technique used is purposive sampling, with 231 samples. Research data were analyzed using multiple regression analysis and additional tests (robustness check) on the islands big in Indonesia. The results showed that 1) the number of daily cases of COVID-19 economic problems significantly affected budget change policies due to the COVID-19 crisis. 2) Social problems have an insignificant negative effect on budget change policies. 3) Economic problems have a significant adverse effect on budget changes. 4) Public attention has a negative significance on budget changes. This research has implications for extending literature related to changes to the Regional Government Budget as a step for handling COVID-19 from the perspective of the Systemic Agenda, as well as providing input to Regional Governments in handling COVID-19, which has an impact on health, social and economic aspects.